Prevalence and incidence of, and risk factors for, HIV-1 infection among factory workers in Ethiopia, 1997-2001. - Mekonnen, Y; Sanders, E; Messele, T; Wolday, D; Dorigo-Zestma, W; Schaap, A; Mekonnen, W; Meless, H; Mihret, W; Fontanet, A; Coutinho, R; Dukers, N (2005)
The study was conducted to determine the prevalence, incidence, and risk factors for HIV infection among factory workers at two sites in Ethiopia. During February 1997-December 2001, a structured questionnaire was used for obtaining information on sociodemographics, sexual behaviour, and reported sexually transmitted infections (STIs) from a cohort of 1679 individuals. Serum samples were screened for antibodies against HIV, Treponema pallidum haemaglutination (TPHA), and herpes simplex virus type 2 (HSV-2). The overall baseline prevalence of HIV was 9.4%-8.5% among males and 12.4% among females. For both the sexes, the factors independently associated with an increased risk of HIV infection were widowhood and having had antibodies against TPHA and HSV-2. The risk factors specific for males were being orthodox Christian, having had a higher lifetime number of sexual partners, and genital discharge in the past five years. The risk factors for females, included low income, one or more rape(s) over lifetime, and casual sex in the last year. The overall incidence of HIV infection was 0.4 per 100 person-years. The highest rate of incidence was observed among young women aged less than 30 years (1 per 100 person-years). The study confirmed that high-risk sexual behaviour and STIs play major roles in the spread of HIV infection in the Ethiopians of both the sexes, but the factors, such as rape and low economic status, make women more vulnerable than men.